A gravity theory of subordinate financialisation - Photis Lysandrou (City, University of London, City Political Economy Research Centre (CITYPERC), 2022)
Recent decades have marked both the globalisation of capitalism following the collapse of communism and its financialisation following the rapid growth of the world's securities markets. These developments have impacted the core-periphery divide in capitalism. In the case of globalisation, the entry of the ex-communist countries into the world capitalist system has swelled the ranks of the emerging capitalist economies (ECEs) that are kept subordinate through the pressures from the advanced capitalist economies (ACEs). In the case of financialisation, the growth of the securities markets has led to a palpable change in the pressures that perpetuate subordination. Where previously the use of authority was the chief source of those pressures, it now plays a secondary role. Absent that authority, and the ECEs would still be held in a subordinate position in global capitalism through the gravitational pull of the ACEs' financial securities markets. The central purpose of this paper is to explain this gravitational pull.
Keywords: 330; subordinate financialisation; gravitational pull of the financial securities markets